Public Perception and Awareness of Health Risks of Climate Change: A Potential for Adaptation and Mitigation in Kenya - Okaka , Fredrick Okoth (African Journal of Education,Science and Technology (AJEST), 2014)
There is widespread scientific consensus that the world‟s climate is changing. This change has been found to have adverse consequences on human health as well as exacerbates health risks. Mounting evidence suggests current and future effects on human health, including injuries and illnesses from severe weather events, floods, and heat exposure; increases in allergic, respiratory, vector-borne, and waterborne diseases; and threats to food and water supplies. Indirect effects may include anxiety and depression. The discourse of climate change must thus be framed from public health perspective with a focus on reducing its impacts. Health consequences of climate change can be a useful lever for enhancing individuals‟ engagement in adaptation and mitigating strategies to climate change. This paper discusses the potentials posed by perception and awareness of health risks of climate change as a step to individual adaption and behaviour change in Kenya. Kenya, like other nations in the world, is faced with the serious threats of climate change to livelihood and human health. Being a developing country, Kenya is more vulnerable to such impacts. However, potentials lie on adaption and mitigation measures of which behaviour change is a critical factor. Research has shown that public risk perceptions strongly influence the way people respond to hazards. When a community or individual perceives a problem to be a very serious threat, then it is likely to initiate appropriate intervention measures, hence the potential of public perception/awareness of health risks of climate change for adaptation and mitigation strategies in Kenya